1996
DOI: 10.4315/0362-028x-59.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Cetylpyridinium Chloride (CPC) Treatment on Poultry Skin To Reduce Attached Salmonella

Abstract: Cetylpyridinium chloride (1-hexadecylpyridinium chloride, CPC) was evaluated for its effectiveness in removing or killing salmonellae attached to poultry skin. Two different treatment methods were used: (i) spraying 0.1% CPC solution at 15 degrees C or 50 degrees C against inoculated skin surface for I min at 138 kPa, and (ii) immersing inoculated skin surface in 0.1% CPC solution at room temperature for either 1 min, 1 min plus 2 min holding without CPC, or 3 min. After rinsing, cells on the skins were enumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 0 publications
2
28
0
2
Order By: Relevance
“…Several studies report that washing poultry carcasses with 0.5 % CPC can reduce up to 2.5 log of Salmonella Typhimurium (Kim and Slavic 1996). In a study by Cutter et al (2000), they sprayed 1 % CPC solution on beef carcass and recorded E. coli O157:H7 and Salmonella Typhimurium reduction up to 5-6 log CFU/cm 2 .…”
Section: Cetylpyridium Chloridementioning
confidence: 99%
“…Several studies report that washing poultry carcasses with 0.5 % CPC can reduce up to 2.5 log of Salmonella Typhimurium (Kim and Slavic 1996). In a study by Cutter et al (2000), they sprayed 1 % CPC solution on beef carcass and recorded E. coli O157:H7 and Salmonella Typhimurium reduction up to 5-6 log CFU/cm 2 .…”
Section: Cetylpyridium Chloridementioning
confidence: 99%
“…Most in vitro studies have evaluated sanitizer ef®cacy against single species bacterial bio®lms (Helke et al 1993;Ronner and Wong 1993;Brown et al 1995;Dhir and Dodd 1995;Kim and Slavik 1996;Frank and Chimielewski 1997;Lindsay and von Holy 1999). However, it has recently been reported that two bacteria present in an in vitro binary bio®lm may enhance each other's survival of sanitizer treatments compared with the corresponding single species bio®lms (Leriche and Carpentier 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Senyawa ini mampu menghambat pertumbuhan L. monocytogenes pada produk-produk sayuran (Wang & Johnson, 1997;Wang & Slavik, 2001), E. coli, L. monocytogenes, S. aureus, dan S. thyphimurium pada daging sapi (Pohlman, 1999;Cutter, et al, 2000;Stopforth et al, 2002;Bosilevac et al, 2004;Lim & Mustapha, 2004;Lim & Mustapha, 2007), serta Salmonella sp. pada produk unggas (Kim & Slavik, 1996;Breen, et al, 1997).…”
Section: Pendahuluanunclassified